Blueprint project technology entrepreneurship / Farah Wahida Jaafar...[et al.] - Jaafar, Farah Wahida; Abd Aziz, Norsabiela; Mohd Radzi, Nur Fadilah Husna; Yusaini Husham, Nur Farahin; Awang, Salmiah
In this millennium and globalization era, there are so many products available at the market for the ease use of the customers outside there as number of people increase from day to day. The globalization nowadays cause the increase of carbon dioxide in the surrounding air which cause the weather and the surrounding to be hot. The increase in the weather temperature had lead people to consume a lot of water as they need to survive in their life. As human, they need at least 8 litres of water per day to survive in their everyday live as they need to travel to many places each single day. Concerning to this problem, our company realized that water is the important element required by the human body to stay healthy and energized to do works. So, to meet the increasing demand of the use of boiled water, our company feel responsible to create a new solar thermos that can make and ease people to drink boiled water at anyway and anytime where the water in the thermos can be easily boil without the used of electricity energy. Related to this situation, we create the solar thermos based on other similar thermos products at the market but added some technology on it. The concept of our product is originated from the existing product at the market but it will smarter because of the technologies provide on it. Our company just want to solve the problem and add more higher technology that can save the uses of electricity automatically eco-friendly stuff and the user are not too worried because they can drink boiled water at anytime as long as there have a solar energy. Therefore, our product are the product that solved the people problem and demanding because that is our company priority. According to Cosmo Online (2015) the statistic of backpackers and traveller are increase, so our solar thermos will provide convenience for the users who like to travel or go hiking. It also can save the cost to pay the electrical bill because it used the solar energy. As we know the solar energy come from the sun where it is renewable, inexhaustible and does not cause environmental pollution.